Pengaruh Terapi Isometric Handgrip Exercise Terhadap Perubahan Tekanan Darah Pada Klien Hipertensi di Wilayah Kerja Puskesmas Babakan - Baik Heni Rispawati; Ernawati; Heny Marlina Riskawaty (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
Hypertension is a chronic disease that is secretly deadly or is often called "the silent killer". A person can be said to be suffering from hypertension if they have systolic blood pressure >140 mmHg and diastolic >90 mmH. The aim of this study was to determine the effect of Isometric Handgrip Exercise therapy on reducing blood pressure in hypertensive clients. This research is a quantitative research with a quasi-experimental approach, namely pretest-posttest with control group with a sample size of 16 respondents for each group. The sampling technique uses purposive sampling. This research was conducted in Cakranegara Selatan Baru Village from 18 June to 22 June 2023. Data collection tools used observation sheets and sphygmomanometers. Data analysis used the Wilcoxon test. The statistical test results showed a significant value of 0.000 <0.05 (systolic) and 0.004 <0.05 (diastolic) so that H₁ was accepted, meaning that there was an effect of isometric Handgrip Exercise on changes in blood pressure in hypertensive clients.